2020
DOI: 10.1177/2333721420966518
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Needs of Deaf Informal Caregivers of Loved Ones with Alzheimer’s and Related Dementia

Abstract: No studies have included the experiences and needs of informal caregivers who are deaf, use American Sign Language (ASL), and care for a loved one with Alzheimer’s disease or related dementias (ADRD). The CDC’s BRFSS Caregiver Module and PROMIS-Deaf Profile measures were administered via an online bilingual English/ASL platform between October 2019 and March 2020. Out of 194 deaf adult signers who completed an online survey, 42 respondents (mean age = 66; SD = 12; 74% White) endorsed informally caring for some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A secondary data study found that Deaf people who reported low educational levels were more likely to be at risk for cardiovascular disease compared with Deaf people with a four-year college degree or more (OR = 5.76) [ 36 ]. Two small-scale self-report studies [ 37 , 38 ] found that more years of education was significantly associated with higher quality of life for Deaf people.…”
Section: Resultsmentioning
confidence: 99%
“…A secondary data study found that Deaf people who reported low educational levels were more likely to be at risk for cardiovascular disease compared with Deaf people with a four-year college degree or more (OR = 5.76) [ 36 ]. Two small-scale self-report studies [ 37 , 38 ] found that more years of education was significantly associated with higher quality of life for Deaf people.…”
Section: Resultsmentioning
confidence: 99%
“…7-9 Specifically, a qualitative study of informal deaf caregivers identified accessibility as a necessary component of dementia care worker training. 1 These findings underscore the importance of providing high-quality, culturally adapted, and sign language–accessible training and educational materials to empower deaf caregivers. Providing the necessary knowledge and tools to deaf caregivers can improve the well-being of those in their care, as well as themselves.…”
Section: Recommendation 2: Deliver Evidence-based Training In Sign La...mentioning
confidence: 95%
“…Providing ADRD resources in a sign language format will improve access to accurate ADRD-related information and improve awareness and health literacy among deaf people who use sign language. 1,4 Disseminating high-quality, culturally adapted, and linguistically aligned videos that are accessible can increase knowledge of ADRD care among deaf people. 5,6 We recommend the following actions for policy makers and advocates in the deaf community:…”
Section: Recommendation 1: Increase Awareness Of Alzheimer’s Disease ...mentioning
confidence: 99%
See 1 more Smart Citation